Social study in democracy evolution (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Democracy is a historical concept that has taken various forms and implementations, though essentially the highest example of the equality of people in life opportunities of all political, economic and social spheres, allows each person to develop his skills, and unleash his potential to achieve self-realization. There is dissimilarity between sophists about the concept of democracy. Some sophists believe that the democracy is a regime which is represented in political aspects such as election and voting..., And Some sophists believe it as a life system that organizes social and economic relations in society, this is called social democracy. Others believe that the democracy is the both a regime and a life system. The expression of democracy in Greek form was inspired in ancient Athens in the fifth century BC, Athenian democracy is considered as of the first models to use contemporary concepts of democratic rule,This research is addressing the democracy with Greek sophists and some of modern sophists. Over time, the meaning of democracy has evolved since the eighteenth century with the emergence of successive democratic regimes in many countries of the world.